ANALISIS PENGETAHUAN GURU DAN SISWA TENTANG WAWASAN BIMBINGAN DAN KONSELING DI SMK NEGERI 2 TANAH PUTIH - Salman Maiza Salman Maiza; Rosmawati '; Sardi Yusuf Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This studyaims to descrybethe level ofknowledgeof teachersandstudentsabout theinsightsof guidance and counselinginSMKNegeri2Tanah Putih, thebackgrounddue to a phenomenonseenin schools, namely: Problemstudyhow the image ofthe teacherandstudentknowledgeabout theinsightsof guidance and counselinginSMK Negeri2Tanah Putih. The method usedinthisresearchisdescriptivemethod. Location of the studyare inSMK Negeri2Tanah Putih. Subjects inthis study wereteachersandstudents of classXIAccounting Departmentandstudents of classXIOffice AdministrationDepartmentatSMK Negeri2Tanah Putih, taken with thesaturatedsampletechnique. Dataanddata collectiontoolwasa questionnaireformteacherandstudentknowledgeabout theinsightsof guidance and counselinginSMKNegeri2Tanah Putih, whichis madebythe researchers themselvesbased on thelatticewithalternativeanswersYES and NO. Data analysis techniqueusingbenchmarkcategoriesbased on thenormal curve, in accordancewith the opinion ofthe JWPphamandSirotnikK.andArlizonR., (1998: 100) andthe percentageformula(Anas Sudijono, 2000:40). Conclusion Theresults ofthis study, basedonthe results ofthe calculation ofbenchmarksknowledge ofteachers andstudentsabout theinsightsof guidance and counselinginSMKNegeri2Tanah Putih, locatedin themiddle category, according to theresults of the analysis. As afollow-up tothis study,the research  hersrecommended thatinterested partiescanfurther increaseteacherknowledgeofguidanceandcounselingby providingtrainingin order toachievethe desired goal. Nextto the researcheris expectedtoconductfurther researchin view ofthe need forknowledge, especiallyguidanceandcounselingis needed inthe formation of characterandattitudeof the nation. Keywords: Teacher Knowledge, GuidanceandCounseling